PROTOTYPE PENGATURAN SUHU BAK BAMBU PADA PROSES PEUYEUMISASI LISTRIK KERAKYATAN - Rakhmadi Irfansyah Putra; Rakhmat Arianto; Duliades Mirsal (PETIR, 2018)
Peuyeumisasi derived from Peuyeum word which means is tapai made from fermented cassava by involving the activity of yeast Saccharomyces cerevisiae. Research conducted from the beginning to the process of testing the Temperature Monitoring System in peuyeumisasi process can be concluded that: Measurement of temperature in peuyeumisasi process to keep the waste temperature remain optimal during the peuyeumisasi process. Temperature montoring system is done automatically and integrated with computer. Tools that provide relevant temperature data information and provide action when the temperature is not optimal.